On the role of speed adaptation and spacing indifference in traffic instability: Evidence from car-following experiments and its stochastic model. (November 2019) - Tian, Junfang; Zhang, H.M.; Treiber, Martin; Jiang, Rui; Gao, Zi-You; Jia, Bin
Highlights: A thorough analysis of the trajectories of the car-following experimental data supports the proposed instability mechanism. The time series of acceleration and the speed difference exhibit striking similarity, and the speed difference plays a more important role on car-following dynamics than spacing. The stochasticity follows a mean reversion process. A heuristic analysis to explain why oscillation grows in a concave pattern was proposed. A new hybrid, stochastic car-following model incorporating speed adaptation and stochasticity was proposed. Abstract: Understanding the mechanisms responsible for the emergence and evolution of oscillations in traffic flow has been a subject of intensive research by numerous scholars. In our previous work, we proposed a new mechanism to explain the generation of traffic oscillations: traffic instability caused by the competition between speed adaptation and stochastic effects. By conducting a closer examination of car following data obtained in a 25-car platoon experiment, we discovered in this work that the speed difference plays a more important role on car-following dynamics than the spacing, and when its amplitude is small, the growth of oscillations is mainly determined by the stochastic factors that follow the mean reversion process; when its amplitude increases, the growth of the oscillations is determined by the competition between the stochastic factors and the speed difference. An explanation is then provided, based on the above findings, to why the speed variance in the oscillatory traffic grows in a concave way along the platoon. We also proposed a mode-switching stochastic car-following model that incorporates the speed adaptation and spacing indifference behavior of drivers, which captures the observed characteristics of oscillation and discharge rate. Finally, our sensitivity analysis shows that the influence on oscillation growth and discharge rate is small by the reaction delay but large by the indifference region boundary.